National interest and Malaysia's Foreign Policy - Wan Shawaluddin Wan Hassan; Zaini Othman; Ramli Dollah; Cheol, Hyun Jeong (2012)
For the Realist, national interest is a crucial concept for explaining states’survival strategy. As national interest of a state is often multifarious in nature, many scholars conclude that national interest could be economic,political, humanitarian, social or environmental interest. National interest is also associated with a security of a state. It is paramount for a state to safeguard their national interest as an iron law of necessity to ensure their security and survival. In this paper, the writers argue that the formulation of Malaysia’s foreign policies is very much determined by what a nation in this case Malaysia, perceive as national interest. Based on historical development, the interplay relation between national interest and foreign policies is discussed in great detail to illustrate that the nature of Malaysia’s foreign policies is primarily geared towards achieving and protecting the national interest at the international level. This article concludes that national interest and foreign policies are intertwined tools vital for enhancing a nation’s well being and survival.